2022
DOI: 10.3390/jmse10121960
|View full text |Cite
|
Sign up to set email alerts
|

Modelling and Simulation Hydrodynamics Processes in Liquefied Natural Gas Transportation Systems

Abstract: Global natural gas resources are growing and are increasingly geographically diverse. A Floating Storage and Regasification Unit (FSRU) is one of the most commonly used vessel types in the global ship fleet due to the possibility of storage, reloading to another ship, and regasifying it for re-injection into the natural gas grid. It is important to control system parameters for reliable technological processes such as tank hydrostatic pressure, vapor pressure, LNG density, LNG temperature, and phase changes be… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
1
1
1
1

Citation Types

0
7
0
1

Year Published

2023
2023
2024
2024

Publication Types

Select...
4
2
1

Relationship

0
7

Authors

Journals

citations
Cited by 8 publications
(8 citation statements)
references
References 29 publications
0
7
0
1
Order By: Relevance
“…In the process of liquefaction, natural gas is purified from undesired substances, such as carbon dioxide, nitrogen, a mixture of propane and butane, and water [29]. Liquefying technology reduces its volume and is also applied to increase the safety of transport and consumption [30,31]. The method consists in changing the form of gas to liquid.…”
Section: Literature Reviewmentioning
confidence: 99%
“…In the process of liquefaction, natural gas is purified from undesired substances, such as carbon dioxide, nitrogen, a mixture of propane and butane, and water [29]. Liquefying technology reduces its volume and is also applied to increase the safety of transport and consumption [30,31]. The method consists in changing the form of gas to liquid.…”
Section: Literature Reviewmentioning
confidence: 99%
“…Studies [19,20] have shown that a decrease in the concentration of carbon monoxide in exhaust gases is possible due to their additional filtration and cooling. At the same time, it was established that similar technological solutions increase aerodynamic resistance in the exhaust pipe.…”
Section: -9969mentioning
confidence: 99%
“…Additionally, the pressure gradient of a slurry pipeline [14] was the index used to quantify the hydrodynamic force acting on the slurry flow. For gas and oil pipelines [15], hydrodynamic forces have mainly been studied by analyzing the drag loss in the transport process [16]. Bhardwaj et al [17] studied the structural safety of pipelines based on multiple burst strength models for corroded pipelines, and they proposed a corroded pipeline model for assessing the reliability of a pipeline's structure.…”
Section: Introductionmentioning
confidence: 99%